Chiral Plasmonic Nanowaves by Tilted Assembly of Unidirectionally Aligned Block Copolymers with Buckling-Induced Microwrinkles - Cho, Junghyun; Hwang, Myonghoo; Shin, Minkyung; Oh, Jinwoo; Cho, Jinhan; Son, Jeong Gon; Yeom, Bongjun (American Chemical Society, 2021)
Chiral-structured nanoscale materials exhibit chiroptical properties with preferential absorptions of circularly polarized light. The distinctive optical responses of chiral materials have great potential for advanced optical and biomedical applications. However, the fabrication of three-dimensional structures with mirrored nanoscale geometry is still challenging. This study introduces chiral plasmonic nanopatterns in wavy shapes based on the unidirectional alignment of block copolymer thin films and their tilted transfer, combined with buckling processes. The cylindrical nanodomains of polystyrene-block-poly(2-vinylpyridine) thin films were unidirectionally aligned over a large area by the shear-rolling process. The aligned block copolymer thin films were transferred onto uniaxially prestrained polydimethylsiloxane films at certain angles relative to the stretching directions. The strain was then released to induce buckling. The aligned nanopatterns across the axis of the formed microwrinkles were selectively infiltrated with gold ions. After reduction by plasma treatment, chiral plasmonic nanowave patterns were fabricated with the presence of mirror-reflected circular dichroism spectra. This fabrication method does not require any lithography processing or innately chiral biomaterials, which can be advantageous over other conventional fabrication methods for artificial nanoscale chiral materials. ？ 2021 American Chemical Society.